Clinical aspects of human rabies in the state of Ceará, Brazil: an overview of 63 cases - Duarte,Naylê Francelino Holanda (2021)
Abstract INTRODUCTION Rabies is considered one of the most relevant public health problems owing to its high fatality rate and the high number of deaths worldwide. METHODS We included patients with human rabies who attended a reference hospital in the state of Ceará during 1976-2019. RESULTS Data were available for 63 out of 171 (36.8%) patients. Of these patients, 48 (76.2%) were attacked by dogs. In recent years, wild animals have been the most common aggressor species (marmosets and bats). Only 39 (70%) patients were initially correctly suspected with rabies. Bites were the most frequent exposure (56; 96%), most commonly on the hands (21; 42%) and the head (9; 18.4%). Only 14 (22%) patients had sought medical assistance before the onset of symptoms, and only one completed post-exposure prophylaxis. The most prevalent signs and symptoms included aggressiveness/irritability (50; 79.4%), fever (42; 66.7%), sore throat/dysphagia (40; 63.5%), and myalgia (28; 44.4%). Hydrophobia was present in 17 patients (22.0%). CONCLUSIONS Most cases of human rabies in Ceará occurred due to the failure to seek medical assistance and/or the failure of the health system in initiating early post-exposure prophylaxis. There is a need for specific information and education campaigns focusing on the cycle of sylvatic rabies as well as prevention measures. Health professionals should undergo refresher training courses on the signs and symptoms of rabies and on the specific epidemiological features of the disease in Brazil.